KOMPOSITUM VERBA DASU DAN PADANANNYA DALAM BAHASA INDONESIA - Tusia Andri Yani; Arza Aibonotika; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses about compound verb of dasu, and its equivalent in Indonesian. The purpose of the research is to describe kind of verb could accompany verb of dasu, the meanings of its, and its equivalent in Indonesian. Data in this research is sentences that contain compound verb of dasu selected from Nihongo Bunkei Ziten and corpus data. This study is used translational equivalent method and sorting determinat technique. The result of this research indicate that the kind of verb that dasu verbs can be accompanied to dasu is continuative verb, movement verb, stative verb, and muishi doushi. Compound verb of dasu meaning is the process of starting verbs, transfer from inside to outside, inward movement (towards the speaker), find, and change.Compound verb of dasu meaning is the process of starting verbs is equivalent with the word starting before the equivalent which is accompanied to dasu. Equivalent of of transfer from inside to outside’s meaning is is paired according to the verb that accompanied it and the meaning it contains. While the equivalent that carry the inward movement (towards the speakers) meaning and find meaning equivalent with the same equivalent verbs accompanied to dasu. Verbs that carry the meaning of change are affixed –me to the equivalent of the basic form of the verb accompanied to dasu.Key words: Compound, Verb, Equivalent